The Clinical Nurse Leader in the Perioperative Setting: A Preceptor Experience. - Wesolowski, Michael S.; Casey, Gwendolyn L.; Berry, Shirley J.; Gannon, Jane (AORN Journal, 2014)
The US Veterans Administration (VA) has implemented the clinical nurse leader (CNL) role nationwide. Nursing leaders at the Malcolm Randall VA Medical Center in Gainesville, Florida, implemented the development of the CNL role in the perioperative setting during the summer of 2012. The perioperative department developed the position in partnership with the University of Florida College of Nursing, Gainesville, Florida. The team developed a description of the roles and experiences of the preceptors, the clinical nurse leader resident, and the University of Florida faculty member. The clinical nurse leader resident's successes and the positive outcomes, such as improved patient outcomes, experienced by the perioperative department demonstrated the importance of the CNL role.